2014
DOI: 10.4103/2279-042x.132707
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo effects of Oxytocin on coagulation of parturient during cesarean delivery by thromboelastography

Abstract: Objective:Oxytocin routinely used as an uterotonic drug in cesarean delivery. Clothing problems, adverse effects on fibrinogen and bleeding were presented as side effects of oxytocin. In in vivo investigation, modest hypercoagulable state was suggested as a side effect for infusion of oxytocin in parturients. In this study, effects of two different infusion rates of oxytocin on coagulation of parturient were evaluated during cesarean delivery.Methods:In a randomized double-blinded clinical trial, 84 healthy pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Butwick and Harter 30 showed that oxytocin at increasing doses led to a hypercoagulable state. A similar effect was seen in vivo 31 . The other uterotonics have not been studied for their effect on coagulation function.…”
Section: Drug Effects On Viscoelastic Testingmentioning
confidence: 56%
See 1 more Smart Citation
“…Butwick and Harter 30 showed that oxytocin at increasing doses led to a hypercoagulable state. A similar effect was seen in vivo 31 . The other uterotonics have not been studied for their effect on coagulation function.…”
Section: Drug Effects On Viscoelastic Testingmentioning
confidence: 56%
“…A similar effect was seen in vivo. 31 The other uterotonics have not been studied for their effect on coagulation function.…”
Section: Drug Effects On Viscoelastic Testingmentioning
confidence: 99%